Application and potential of shape memory alloys for dowel-type connections in timber structures. Issue 6 (2nd November 2022) - Schwarze, R.; Braun, M.; Seim, W.; Krooß, P.; Vollmer, M.; Niendorf, T.
ABSTRACT: The present study aims at identifying and analyzing challenges and prospects related to the use of pseudoelastic shape memory alloys for well-established double shear connections in timber engineering. The unique behavior of shape memory alloys will allow to bear large reversible deformations without loss of cohesion. Thereby, the main objective of the present work is to study the behavior of a connection that is able to stay completely reversible even upon very large deformations. In this context, the stiffness of the connection as well as functional and structural integrity and damping behavior have been improved by stepwise adaption of the detailing. Proof of concept is provided, and current limitations are discussed, based on the application of bolts made from a commercially available shape memory alloy.